The Role of Economic Growth, Income Inequality, and Social Assistance in Shaping Poverty Dynamics in Central Java - Maulana Ghani Yusuf; Tangguh Pratysto (Transpublika Publisher, 2026)
Poverty remains a development challenge, particularly those with low economic growth and poorly distributed social welfare. Despite high economic growth, poverty reduction often remains uneven, demonstrating the complex interactions between growth, income distribution, labor market conditions, and the social assistance safety net. This study aims to examine the factors influencing poverty, their relationship to economic growth, income inequality, unemployment, and the social assistance safety net in Central Java. Using a quantitative panel data methodology, this study analyses data on the variables used from 2019 to 2023. A fixed effects model with robust standard errors is used to consistently and effectively estimate the relationship between the determinants of poverty. The results of this study indicate that economic growth, particularly GDP, can significantly reduce poverty. Then income inequality also significantly influences poverty dynamics. Social assistance is positively related to poverty, meaning it effectively serves as a tool to help people avoid falling into poverty. Meanwhile, unemployment has an insignificant impact on poverty. It follows from the above that the poverty-reduction strategy in Central Java should not be oriented solely to the growth path but should be coupled with tax reform integrated into social assistance packages to improve targeting efficiency and sustainability.